2020
DOI: 10.1108/nfs-08-2019-0270
|View full text |Cite
|
Sign up to set email alerts
|

Associations between white blood cells count and obesity in apparently healthy young adults

Abstract: Purpose The elevated white blood cells (WBCs) count has been reported to be a predictor of cardiovascular diseases, diabetes, hypertension and metabolic syndrome. This study aims to determine the associations between WBCs count and obesity in apparently healthy young adults. Design/methodology/approach In this cross-sectional study, the authors evaluated the body mass index (BMI) in 392 apparently healthy young adults of both sexes. The WBCs count was measured using standard counter techniques. The inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In accordance with our results, a study involving a cohort of young healthy women reported a significantly positive relationship between WBC and body fat (%), WC, and CRP, but not with IL-6 [52]. Additionally, other studies reported the same differences and correlations between WBC and BMI in apparently healthy young adults and even in adolescents [53,54]. Furthermore, an elevated WBC within the normal range can predict the incidence of and serve as an independent risk factor for type 2 diabetes, hypertension, and MS among young obese individuals [55][56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, a study involving a cohort of young healthy women reported a significantly positive relationship between WBC and body fat (%), WC, and CRP, but not with IL-6 [52]. Additionally, other studies reported the same differences and correlations between WBC and BMI in apparently healthy young adults and even in adolescents [53,54]. Furthermore, an elevated WBC within the normal range can predict the incidence of and serve as an independent risk factor for type 2 diabetes, hypertension, and MS among young obese individuals [55][56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…We observed an association between current BMI and naive B cells, memory B cells, naive CD4 T cells, and memory‐activated CD4 T cells, possibly because BMI and body weight were positively correlated with WBC counts in apparently healthy young adults (higher in women) [39]. As skewed WBC proportions due to differences in BMI could have influenced our BMI analyses, we included these estimated cell proportions in our fully adjusted models [40].…”
Section: Discussionmentioning
confidence: 99%